REALITAS KONTEMPORER ISLAM DAN KERAGAMAN AMERIKA SERIKAT DAN KANADA - Harahap, Aziddin (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2020)
The history of Islam in the United States dates back to around the 16th century, when EstevÃ¡nico of Azamor was the first Muslim recorded in North American history.1 However, most researchers in studying the arrival of Muslims in the US have focused more on the arrival of immigrants who came from the Middle East in the late 19th century. This migration of Muslims to the US took place over a different period, which is often called the "wave", although experts do not always agree on what caused these waves. In Washington. Mosques are the main places of worship for a Muslim. In the US, there are around 1,209 mosques, of which the largest is the Islamic Center of America located in Dearborn, Michigan. Built in 2005, the Mosque can accommodate more than 3,000 worshipers who continue to grow in the area. With fewer than 100 units actually designed as mosques from the start, most Muslim worshipers in the US originally worshiped in buildings originally erected for other purposes, such as former fire stations, theaters, warehouses and shops. The largest number of mosques in the US is in the State of California, which is about 227 units in 2001.